The effectiveness of an interactive simulation-based WDPP tool in fostering student comprehension of complex problem solving / Norhusna Mohamad Nor and Nor Aida Zubir - Mohamad Nor, Norhusna; Zubir, Nor Aida (Universiti Teknologi MARA, 2023)
Complex problem solving is regarded as one of engineering's central activities. However, students consistently find complex interactions involving multiple parameters to be tedious and perplexing in the classroom. Hence, an interactive simulation tool based on the Wolfram Demonstration Project platform (WDPP), which was adopted from www.learncheme.com, is used as a teaching aid to enlighten students about the complex interactions of multiple parameters in engineering calculations in a simple and engaging manner. This interactive simulation tool was implemented in selected chapters of the Separation Processes course as a pilot test to evaluate its effectiveness as a new and alternative teaching aid in the classroom based on actual student attainment of course outcome (CO) and questionnaires. The two (2) COs include the attribute of i) applying engineering knowledge and/or fundamentals (CO1, PO1) and ii) solving complex engineering problems (CO2, PO2). Analysis of the assessment data revealed that, the average student attainment for CO1 and CO2 was 81.43% and 81.13%, respectively, for the chapters in which interactive simulation was used. In contrast, the average CO1 and CO2 attainment for non-adopted chapters was 75.40% and 81.99%, respectively. These results suggest that the student’s achievement improved decently based on coherent data of students’ actual attainment in both CO average and CO density when the interactive simulation-based WDPP was used in the class. In addition, 92.59% of students agreed that the use of interactive simulations in classroom was useful, interesting, and engaging. These results shed new insight on the use of interactive simulation-based WDPP as an alternative teaching aid or learning platform for enhancing the content and delivery of the curriculum.